Molecular genetic analysis of virus isolates from wild and cultivated plants demonstrates that East Africa is a hotspot for the evolution and diversification of Sweet potato feathery mottle virus - Tugume, Arthur K.; Cue´ Llar, Wilmer J .; Mukasa, Settumba B.; Valkonen, Jari P. T. (Molecular ecology, 2010)
Sweet potato feathery mottle virus (SPFMV, genus Potyvirus) is globally the most common pathogen of cultivated sweet potatoes (Ipomoea batatas; Convolvulaceae). Although more than 150 SPFMV isolates have been sequence-characterized from cultivated sweet potatos across the world, little is known about SPFMV isolates from wild hosts and the evolutionary forces shaping SPFMV population structures. In this study, 46 SPFMV isolates from 14 wild species of genera Ipomoea, Hewittia and Lepistemon (barcoded for the matK gene in this study) and 13 isolates from cultivated sweet potatoes were partially sequenced. Wild plants were infected with the EA, C or O strain, or co-infected with the EA and C strains of SPFMV. In East Africa, SPFMV populations in wild species and sweet potato were genetically undifferentiated, suggesting inter-host transmission of SPFMV. Globally, spatial diversification of the 178 isolates analysed was observed, strain EA being largely geographically restricted to East Africa. Recombination was frequently detected in the 6K2-VPg-NIaPro region of the EA strain, demonstrating a recombination ‘hotspot’. Recombination between strains EA and C was rare, despite their frequent co-infections in wild plants, suggesting purifying selection against strain EA⁄C recombinants. Positive selection was predicted on 17 amino acids distributed over the entire coat protein in the globally distributed strain C, as compared to only four amino acids in the coat protein N-terminus of the EA strain. This selection implies a more recent introduction of the C strain and a higher adaptation of the EA strain to the local ecosystem. Thus, East Africa appears as a hotspot for evolution and diversification of SPFMV.
Keywords: East Africa; Ipomoea; Potyvirus; Recombination; Selection pressure; Wild plant species